Observation of relaxation of molecular spins in CH₄ and CD₄ crystals in thermal conductivity experiment - Pisarska, E.; Stachowiak, P..; Jeźowski, A. (Физика низких температур, 2007)
The paper reports preliminary results on the kinetics of the molecular spin conversion in solid methane (CH₄) and deuterated methane (CD₄), obtained through thermal conductivity measurements in the temperature range 2–10 K.